2016
DOI: 10.3892/ijo.2016.3431
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the MAP kinase pathway in astrocytoma cells using a recombinant anthrax lethal toxin as a way to inhibit cell motility and invasion

Abstract: Malignant astrocytomas are highly invasive into adjacent and distant regions of the normal brain. Understanding and targeting cancer cell invasion is an important therapeutic approach. Cell invasion is a complex process that replies on many signaling pathways including the mitogen-activated protein (MAP) kinase (MAPK). In many cell lines, the use of MAPK-targeted drugs proved to be a potential method to inhibit cancer cell motility. In the present study, we use a recombinant anthrax lethal toxin (LeTx), which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 36 publications
(38 reference statements)
1
22
0
Order By: Relevance
“…Pull-down assays were performed using the RhoACdc42/Rac Activation Assay Combo Kit (Cell BioLabs) as previously described [65] and following the manufacturer’s instructions. Briefly, cell lysates were incubated with GST-RBD (Rhotekin binding domain) for 1 h at 4 °C with gentle agitation.…”
Section: Methodsmentioning
confidence: 99%
“…Pull-down assays were performed using the RhoACdc42/Rac Activation Assay Combo Kit (Cell BioLabs) as previously described [65] and following the manufacturer’s instructions. Briefly, cell lysates were incubated with GST-RBD (Rhotekin binding domain) for 1 h at 4 °C with gentle agitation.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, we noticed the complexity and interconnectedness between VEGF and Rho-related pathways which benefit cancer cells in multiple aspects which include but are not limited to angiogenesis, migration, and invasion. Due to the complications associated with the untargeted cancer therapies (chemo-and radiotherapy), approaches targeting specific characteristics and pathways of tumors must be explored [80,[125][126][127][128][129]. Therefore, targeting these interaction factors that are produced and secreted by the tumor cells might exhibit promising therapeutic potential.…”
Section: Resultsmentioning
confidence: 99%
“…Our lab has further demonstrated that targeting the MAP kinase pathway in astrocytoma cells by using a recombinant anthrax lethal toxin inhibits cell motility and invasion by deregulating the Rho GTPases. In this context, cells treated with the toxin revealed a higher density of stress fibers, potentially indicating an increase in the activity of RhoA [80]. Upon inspection, treated cells did in fact exhibit a higher expression of activated RhoA as well as a higher tendency to adhere properly [80].…”
Section: Rho Gtpasesmentioning
confidence: 91%
See 1 more Smart Citation
“…For example, several studies have shown that melanoma cells that carry N-Ras mutations are not sensitive to the LF-mediated inhibition of the MAPK pathway, while those carrying a V600E B-Raf mutation are sensitive to the inhibition of this pathway (25,27). Previously, it was also demonstrated that LeTx successfully decreased cellular motility and invasion of glioblastoma cells by increasing their adhesion via an increase in RhoA activity (28).…”
Section: Introductionmentioning
confidence: 99%